1992
DOI: 10.1017/s0022112092004361
|View full text |Cite
|
Sign up to set email alerts
|

Spectral large-eddy simulation of isotropic and stably stratified turbulence

Abstract: We first recall the concepts of spectral eddy viscosity and diffusivity, derived from the two-point closures of turbulence, in the framework of large-eddy simulations in Fourier space. The case of a spectrum which does not decrease as $k^{-\frac{5}{3}}$ at the cutoff is studied. Then, a spectral large-eddy simulation of decaying isotropic turbulence convecting a passive temperature is performed, at a resolution of 1283 collocation points. It is shown that the temperature spectrum tends to follow in the energet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
169
1
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(218 citation statements)
references
References 68 publications
(45 reference statements)
24
169
1
4
Order By: Relevance
“…͑10͒, this is equivalent to modeling the unresolved energy transfer T Ͼ in terms of the resolved field. One standard model 5,6 is…”
Section: Subgrid Scale Models Of Energy Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…͑10͒, this is equivalent to modeling the unresolved energy transfer T Ͼ in terms of the resolved field. One standard model 5,6 is…”
Section: Subgrid Scale Models Of Energy Transfermentioning
confidence: 99%
“…Although it is no longer often applied in its original form, it is the basis of much more commonly used models like the dynamic model, 2 various ''mixed'' models, 3,4 and more specialized spectral SGS models for homogeneous turbulence. 5,6 Eddy viscosity models attempt to describe the transfer of energy between the resolved and unresolved scales. But the subgrid scales not only act as a sink and source of energy, they also contribute, through nonlinear interactions, to the temporal decorrelation of the resolved scales.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kerr [1985] found that the kurtosis (or flatness factor) for the scalar derivative is larger than the velocity derivative for isotropic turbulence, suggesting that the scalar field is more intermittent than the velocity field. Using direct and large-eddy simulations, Metais and Lesieur [1992] found that for stably stratified homogeneous decaying turbulence, the pdf's of velocity and scalars exhibit near-Gaussian behavior, while the pdf's of scalar gradients have long exponential tails. A number of laboratory experiments were also carried out to quantify the scalar pdf and its relationship to the velocity pdf's for nonisotropic turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…Going back to the velocity formulation, this model can also be interpreted as a selective version of the gradient model (39), where only dissipation directions are kept in the turbulent viscosity tensor, avoiding the numerically unstable backward transfer of energy. In [14] 4 an implementation procedure of this model was derived in order Figure 1.…”
Section: Anisotropic Selective Modelmentioning
confidence: 99%
“…This model is reminiscent to a selective model proposed by David [18] in the context of the so-called structure-function model of Metais and Lesieur [39]. The idea is to apply a turbulence model only in regions of intense vortex activity and where the flow is strongly three-dimensional.…”
Section: Smagorinsky Selective Modelmentioning
confidence: 99%